2019
DOI: 10.1002/jcp.28635
|View full text |Cite
|
Sign up to set email alerts
|

An endoplasmic reticulum stress regulator, Tmbim6, modulates secretory stage of mice molar

Abstract: To understand the role of endoplasmic reticulum (ER)-stress in mice molar development, we studied Tmbim6 that antagonizes the unfolded protein response, using Tmbim6 knockout (KO) mice and in vitro organ cultivation with knocking down using small interfering RNA. During molar development, Tmbim6 is expressed in developing tooth at E14-E16, postnatal0 (PN0), and PN6. Mineral content in Tmbim6 KO enamel was reduced while dentin was slightly increased revealing ultrastructural changes in pattern formation of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In this study, we hypothesized that in the exposed dentin and pulp complex, ER stress would be occurred unavoidably to repair the dentin structure and maintain the vitality of the pulp as examined in other wound sites 17,19,20 . In in ammation condition, a number of studies revealed the vicious circle of escalation of pathological conditions between ER stress and in ammation responses 26,37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we hypothesized that in the exposed dentin and pulp complex, ER stress would be occurred unavoidably to repair the dentin structure and maintain the vitality of the pulp as examined in other wound sites 17,19,20 . In in ammation condition, a number of studies revealed the vicious circle of escalation of pathological conditions between ER stress and in ammation responses 26,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Formation of dentin is mainly contributed by cellular physiology of odontoblasts. These speci c secreting cells are precisely regulated and modulated by ER regulation and vesicle tra cking to form the speci cally featured dentin matrices through protein synthesis, folding, tra cking, secretion, and patterned apposition 17,19,20 . Previous studies reported that modulation of ER stress would be an important cellular pathway for differentiation and maintenance of dentin 18,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ImageJ software was used to quantify all morphologic data as described previously. 31 At least three different figures from three different samples were used for the statistical analysis.…”
Section: Photography and Image Analysismentioning
confidence: 99%
“…Previous report suggested that ER stress would affect formation of dentin. For instance: when ER stress regulator gene, Tmbim6 was knocked out, the dentin and enamel structures were disturbed by altering odontoblast and enamel differentiation ( Aryal et al, 2019 ). Mutated dentin forming genes of which could cause Dentinogenesis Imperfecta and Dentin Dysplasia may cause a high level of ER stress ( Brookes et al, 2014 ; Brookes et al, 2017 ; Liang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%